Економія енергії у нашому будинку – це наш особистий внесок у зміцнення енергетичної безпеки України - Оберська, Н. В.; Михайлишин, М. С. (Energy and Automation, 2017)
SAVING ENERGY IN OUR HOUSE IS OUR PERSONAL CONTRIBUTION TO STRENGTHENING ENERGY SECURITYN. V. Оberska, M. S. Mykhailyshyn  ThedevelopmenteconomyofUkrainelargelydependsonsolvingthetaskofprovidingenergysources.  InsufficientscopeofownenergysourcesforcestheUkrainianauthoritiestotakethedecisiononsignificantimports. Intheconditionofreductionworldreservesofhydrocarbonsandgrowthoftheirprices, thesolutionofenergyproblemsonlywiththehelpofimportsisinsufficient. Today, theworldtriestosolvetheproblemofenergysourcesbasedonnewapproaches, infoundationare: first, improvementofthetechnologicalprocessfromthepointofviewofintensityofproduction; second, thedevelopmentofenergy-saving; third, theexpansionofproductionofenergybyaccountofrenovationsources.OneofthemaintasksoftheUkrainianstateis a significantreductionofinefficientconsumptionofenergyresources. Tosolvethisproblemisimpossiblewithout a purposefulenergypolicywhereadequatelytookintoaccountthepossibilityofUkraineastoownproductionofhydrocarbons, developmentofrenewableenergyandenergyefficiency, transitioneconomicstowideapplicationinmanufacturinginnovation. Tosolvethistaskitisnecessarytofocusontheanalysisofthemostimportantaspectsoftheproblemandtospecifyways, meansandmethodsofitssolution. Thismaterialshowstheachievementofenergypolicyingeneralandenergy- savingpolicy, inparticularontheexampleofitsownhome.Energy- savingmeansreasonableenergyuseatalllevelsoftheconversionthatarefromtheextractionofprimaryenergysourcestotheconsumptionofalltypesofenergyend-users.Energy- savingmeasuresmaybedifferent. Oneofthemosteffectivewaystoincreasetheefficiencyofenergyuseisapplicationofmodernenergy-savingtechnologies.Theproblemofenergy- savingisparticularlyrelevantforUkraine, becausewearedependentonsuppliesofenergysourcesfromothercountries. Therefore, economyincombinationwithsimultaneoustransitiontouseoflocalresources.Efficientuseofthermalenergy, intheend, isnottoodifficultcase. Inmostcasesitisthedecisionoftwoquestions: changinghabitsandeliminatingtheheatlossbyimprovingisolation.Inthearticlepresents a listofourownideasofreducingtheamountofenergyconsumedthatwehaveaccomplishedandwanttoshareownexperiencewithothers.Wedonotpretendtoanyscientificdiscoveries. Justfocusattentiononknownbutslightlyforgottennuances.Theresultsofthestudypresenttheinterestforexpertsofquestiononenergy- savinginfindingofoptimalsolutionsforincreasingtheenergyefficiencyofourhome. Mainmeasurestoreduceenergyconsumptioninresidentialbuildingsareestablished. A promisingdirectiontoreducetheelectricpowerandincreasingenergyefficiencyofthehouseproductionistheinstallationofprotectivescreens, newwindows, ventilationofroomsandother. Wemade a numberofsomesimpleactivitiesthatwillallowustoreducetheamountofenergyconsumedby 30%.